2016
DOI: 10.1037/xlm0000241
|View full text |Cite
|
Sign up to set email alerts
|

Similar task features shape judgment and categorization processes.

Abstract: The distinction between similarity-based and rule-based strategies has instigated a large body of research in categorization and judgment. Within both domains, the task characteristics guiding strategy shifts are increasingly well documented. Across domains, past research has observed shifts from rule-based strategies in judgment to similarity-based strategies in categorization, but limited these comparisons to 1 prototypical environment, a linear task structure, and a restricted set of strategies. To systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 73 publications
7
61
0
Order By: Relevance
“…Beyond that, our findings more closely followed the simulations with a Radial Basis Function kernel than what would have been expected if participants had extrapolated more linearly (e.g. Busemeyer et al, 1997;Hoffmann, von Helversen, & Rieskamp, 2016). Using an RBF kernel, our model predicted a relatively small difference in choice proportions between the exotic-novel and ordinary-novel options, but the difference could have been larger if extrapolation relied on a different kernel which does not underestimate the average reward of the exotic-novel option.…”
Section: Discussionsupporting
confidence: 85%
“…Beyond that, our findings more closely followed the simulations with a Radial Basis Function kernel than what would have been expected if participants had extrapolated more linearly (e.g. Busemeyer et al, 1997;Hoffmann, von Helversen, & Rieskamp, 2016). Using an RBF kernel, our model predicted a relatively small difference in choice proportions between the exotic-novel and ordinary-novel options, but the difference could have been larger if extrapolation relied on a different kernel which does not underestimate the average reward of the exotic-novel option.…”
Section: Discussionsupporting
confidence: 85%
“…We found that the best overall model was a linear regression combined with an UCB sampling strategy. This means that participants adapted well to the overall task structure, which was set up to be linear, a finding which is in line with previous work showing that participants rely more on rule-based than similarity-based reasoning in simple linear environments (Hoffmann, von Helversen, & Rieskamp, 2016). Moreover, they sampled inputs to learn about both the overall shape of the function as well as the location of high outputs.…”
Section: Discussionsupporting
confidence: 83%
“…In the nonlinear environment, they tend to adopt a similarity based strategy, predicting values based on how similar the item at hand is to previously experienced items stored in memory (e.g. Hoffmann et al, 2016;Ashby & Maddox, 2011). Participants first underwent a training phase in which they were given the true function values, y, as feedback.…”
Section: Methodsmentioning
confidence: 99%
“…Nosofsky, 1984), and the cognitive processes behind them remain mysterious. Influential models of both category learning (concepts with discrete predicted variables) and function learning (respectively continuous; which we study here), only model predictions and thus cannot easily account for confidence judgements (Hoffmann, von Helversen, & Rieskamp, 2016;Mc-Daniel & Busemeyer, 2005). In contrast, confidence has been extensively studied in perceptual decision making and sensorimotor learning (Pleskac & Busemeyer, 2010;Moran, Teodorescu, & Usher, 2015;Körding & Wolpert, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation